Web GIS of Tourism: Voyage and Forecast - Beri Noviansyah; Cholid Fauzi; Akhmad Bakhrun; Lena Lestary (University of Technology Yogyakarta, 2023)
Web GIS is a kind of distributed information system, which consists of a client and a server, where the server is the GIS server and the client is a web application, desktop application, or mobile application. With the rapid development of technology, increasingly mature GIS technology has been applied in various fields, one of which is tourism. By using a web GIS, reviews related to a tourism object, and tourist locations in a particular area can be easily presented on a website. By utilizing this geographic information system, the potential of tourist attractions and public facilities can be mapped to the maximum, so that tourists can find a place more efficiently and not take long. This study aims to find out the further study the tourism GIS web research over the last 3 years. This study uses the Systematic Literature Review (SLR) method where the search for the required papers comes from an electronic database obtained using the Vos Viewer and Publish or Perish software